Evaluation of Clinical and Pathological Characteristics and Routine Treatment of Patients with Prostate Cancer in Six Referral Centers in Iran: A Pilot Non-interventional, Multicenter Study - Mafi, Ahmad R; Motlagh, Ali G; Mofid, Bahram; Salek, Roham; Hemati, Simin; Mosalaei, Ahmad; Esnaashari, Omid (Reports of Radiotherapy and Oncology, 2021)
Background: Prostate cancer is the second most common malignancy among Iranian men after stomach cancer. To understand the nature of the disease and plan and develop a population-based cancer registry, it is essential to recognize the clinical and pathological characteristics of the tumors, as well as treatment results. Objectives: The present study aimed to evaluate the clinical and pathological characteristics of prostate cancer and evaluate the routine practice, including treatment outline and results of treatment in six referral centers in Iran. Methods: This prospective observational pilot study recruited patients with prostate cancer between April 2015 and October 2015 at six referral centers in Iran. The participating physicians included consecutive patients according to inclusion criteria. Demographic, clinicopathologic, and treatment data were collected by the physicians using an electronic case report form (eCRF). The patients were followed for 18 months, and during this period, four visits were scheduled for each patient to collect the data. Results: A total number of 102 patients from six centers in five different cities of Iran were included in the study. Sixty-seven (65.7%) patients were diagnosed by needle biopsy as the first diagnostic method, 23 (22.5%) by radical prostatectomy, and 12 (11.8%) by open prostatectomy. Total at-risk times of patients for overall survival (OS) and progression-free survival (PFS) were 1480.9 and 1437 months, respectively. Median (IQR) values of OS and PFS were 18.2 (9.2 - 20.5) and 18.2 (6.8 - 20.4) months, respectively. Forty (39.2%) patients underwent surgery, 58 (56.8%) underwent radiotherapy, and 13 (12.7%) received chemotherapy. Twenty-nine (28.4%) patients experienced adverse events over the follow-up period. Eight deaths were reported that were unrelated to treatment adverse effects. Conclusions: This pilot registry could serve as a valuable tool for the development of a comprehensive nationwide registry for patients with prostate cancer in Iran.